SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SANTRI BERKUALITAS PADA PONDOK PESANTREN NUR MEDINA PONDOK CABE DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Kusuma, Bagas Kusuma; Natsir, Fauzan; Fitriansyah, Aswin (Institut Sains dan Teknologi Al-Kamal, 2026)
Nur Medina Islamic Boarding School Pondok Cabe conducts a student quality selection process aimed at providing appreciation to the best students managed by the boarding school. However, this selection process is still carried out manually, which may lead to subjectivity and inefficiency in decision making. This study aims to design and develop a decision support system to determine high-quality students using the Simple Additive Weighting (SAW) method. The SAW method is applied because it is able to determine the best alternative based on the weighted summation of each predetermined criterion. The system design is modeled using Unified Modeling Language (UML). The results of the application of the SAW method are in the form of a ranking of students as a quality alternative with the highest V value, namely V4 = 0.78 with a participant named Ali Akbar. The developed system is expected to assist the Islamic boarding school management in selecting high-quality students objectively, systematically, effectively, and accurately.